The need for virtual reality simulators in dental education: A review - Elby Roy; Mahmoud M. Bakr; Roy George (Elsevier, 2017)
Virtual reality simulators are becoming an essential part of modern education. The benefits of Virtual reality in dentistry is constantly being assessed as a method or an adjunct to improve fine motor skills, hand-eye coordination in pre-clinical settings and overcome the monetary and intellectual challenges involved with such training. This article, while providing an overview of the virtual reality dental simulators, also looks at the link between virtual reality simulation and current pedagogical knowledge. Keywords: Virtual reality, Dental education, Dental simulators